137 P53-DEPENDENT PACLITAXEL SENSITIVITY IN ENDOMETRIAL CANCER. (1st January 2006) - Elmaoued, R.; Holmes, A.; Nguyen, T.; Dai, D.; Leslie, K. K.
Abstract : There are two major pathogenetic variants of endometrial carcinoma, namely type I and II endometrial carcinoma (EC). Type I is composed mostly of endometroid carcinoma and related to estrogen overexposure without progesterone differentiating effect. Type II is often nonendometroid including papillary serous carcinoma (UPSC) and clear cell EC. UPSC accounts for only 10% of all cases but is responsible for 50% of all treatment failures. These two groups seem to evolve via divergent pathways and contain distinct genetic abnormalities. P53 mutation is much more common in UPSC with about 90% of tumors containing the mutation. Such unique genetic backgrounds in these two tumors may also influence their response to chemotherapies. Paclitaxel's cytotoxic effects were often enhanced in tumors carrying p53 mutations. Paclitaxel is one of the most effective chemotherapeutic agents, but its effect is modest in EC. We have characterized two EC cell lines, Ishikawa (H) and Hec50co (CO) cells, and used them to model type I and II EC. Genetic studies have shown that CO cells have a p53 mutation and are negative for estrogen and progesterone receptor. Tumors created from CO cells had features similar to UPSC. In contrast, H cells have wild-type p53, are positive for ER and PR, and developed into a more differentiated phenotype in vivo. Paclitaxel significantly inhibited CO xenograft growth in athymic mice by reducing tumor size and weight. The IC50 for paclitaxel was 14 nM in CO cells. However, H cells were more resistant to paclitaxel with and IC50 of 71 nM, which is significantly higher than CO cells. It has been reported that tumors with a p53 mutation are more sensitive to paclitaxel. Indeed, when p53 was knocked down by the RNA interference in H cells, its IC50 value was reduced to 8.2 nM, 8.5 times more sensitive than parental cells, suggesting that loss of p53 function may enhance cancer response to paclitaxel. H cells with p53 knockdown had a higher percentage of cells undergoing apoptosis than parental H cells. Our studies suggest that endometrial cancer may respond differently to paclitaxel and that UPSC may benefit more from paclitaxel-based therapy.